Effect of cenosphere and specimen crack lengths on the fracture toughness of Al6061-SiC composites (Fracture and Structural Integrity, 2022)
Main aim of this work is to investigate the influences of the addition of cenosphere and specimen crack length on the fracture toughness of Al6061-SiC composites. The experimental analysis was carried out for 3, 6 and 9 wt% proportions of cenosphere with the 3 wt% of SiC as reinforcements in the aluminum 6061 matrix for various crack lengths. The fracture toughness of Al6061-SiC-Cenosphere hybrid composites was estimated using compact tension (CT) specimen for the said compositions. The CT specimens were prepared, according ASTM E399 standard, for different crack length to width (a/W=0.3-0.6) ratios. From the experimental outcomes, it is identified that the fracture toughness of the hybrid composite increases upto the 6wt% of cenosphere and further increment in the cenosphere causes the decrement in the values. It is also found that the load bearing capacity and fracture toughness of the hybrid composite decreases with increment in the a/W ratios of the CT specimen.
Keywords: Cenosphere; fracture toughness; CT specimens; a/W ratios; hybrid composites